Immune checkpoint inhibitor– and phosphatidylinositol-3-kinase inhibitor–related diabetes induced by antineoplastic drugs: two case reports and a literature review - Gao, Yue; Zhong, Mingyao; Gan, Lulu; Xiang, Cheng; Li, Ling; Yan, Yimin (Frontiers in Endocrinology, 2023)
Immune checkpoint inhibitor (ICI)-and phosphatidylinositol-3-kinase inhibitor (PI3Ki)-related diabetes mellitus are common side effects of anti-tumor drug use that present mainly as hyperglycemia. Here, we present two case reports of diabetes mellitus caused by the use of toripalimab and alpelisib, respectively, in cancer treatment, and a comprehensive, comparative review of the literature on these forms of diabetes. Case 1 presented with diabetic ketoacidosis and was diagnosed with ICIrelated diabetes mellitus and treated with insulin. Case 2 was diagnosed with PI3Kirelated diabetes mellitus, and her blood glucose level returned to normal with the use of metformin and dapagliflozin. We systematically searched the PubMed database for articles on ICI-and PI3Ki-related diabetes mellitus and characterized the differences in clinical features and treatment between these two forms of diabetes.